Which equation represents the pattern in the table below?
Sal’s and Carrie’s Ages
Sal
3
5
8
13
15
Carrie
7
9
12
17
19
(1 point)
Responses
s = c + 4
s = c + 4
s = 4c
s = 4 c
c = s + 4
c = s + 4
c = 4s
c = 4 s
11 answers
The equation that represents the pattern in the table is c = s + 4.
Which equation matches the statement: “The sum of –4x and 2 is 9”?
(1 point)
Responses
–4x + 2 = 9
–4 x + 2 = 9
–4x + 9 = 2
–4 x + 9 = 2
–4x(2) = 9
–4 x (2) = 9
–4x – 2 = 9
(1 point)
Responses
–4x + 2 = 9
–4 x + 2 = 9
–4x + 9 = 2
–4 x + 9 = 2
–4x(2) = 9
–4 x (2) = 9
–4x – 2 = 9
The equation that matches the statement "The sum of -4x and 2 is 9" is -4x + 2 = 9.
Solve. x – 6 = –18
(1 point)
Responses
x = –24
x = –24
x = –12
x = –12
x = 12
x = 12
x = 6
(1 point)
Responses
x = –24
x = –24
x = –12
x = –12
x = 12
x = 12
x = 6
To solve the equation x - 6 = -18, you need to isolate the variable x.
Adding 6 to both sides of the equation, we have:
x - 6 + 6 = -18 + 6
Simplifying, we get:
x = -12
So, the solution to the equation is x = -12.
Adding 6 to both sides of the equation, we have:
x - 6 + 6 = -18 + 6
Simplifying, we get:
x = -12
So, the solution to the equation is x = -12.
Solve. 4x + 3 = 47
To solve the equation 4x + 3 = 47, you need to isolate the variable x.
First, subtract 3 from both sides of the equation:
4x + 3 - 3 = 47 - 3
This simplifies to:
4x = 44
Next, divide both sides of the equation by 4 to solve for x:
4x / 4 = 44 / 4
This simplifies to:
x = 11
The solution to the equation is x = 11.
First, subtract 3 from both sides of the equation:
4x + 3 - 3 = 47 - 3
This simplifies to:
4x = 44
Next, divide both sides of the equation by 4 to solve for x:
4x / 4 = 44 / 4
This simplifies to:
x = 11
The solution to the equation is x = 11.
Solve. one-thirdx = 12
To solve the equation one-third x = 12, you need to isolate the variable x.
First, multiply both sides of the equation by 3 to get rid of the fraction:
(3) * (one-third x) = (3) * 12
This simplifies to:
x = 36
So, the solution to the equation is x = 36.
First, multiply both sides of the equation by 3 to get rid of the fraction:
(3) * (one-third x) = (3) * 12
This simplifies to:
x = 36
So, the solution to the equation is x = 36.
Solve. 3x + 3 = 21
To solve the equation 3x + 3 = 21, you need to isolate the variable x.
First, subtract 3 from both sides of the equation:
3x + 3 - 3 = 21 - 3
This simplifies to:
3x = 18
Next, divide both sides of the equation by 3 to solve for x:
3x / 3 = 18 / 3
This simplifies to:
x = 6
The solution to the equation is x = 6.
First, subtract 3 from both sides of the equation:
3x + 3 - 3 = 21 - 3
This simplifies to:
3x = 18
Next, divide both sides of the equation by 3 to solve for x:
3x / 3 = 18 / 3
This simplifies to:
x = 6
The solution to the equation is x = 6.